Developmentof Dominant Basic Motion Assessment Model (Locomotor, Non Locomotor, Manipulative) Children Tuna Grahita - Suprayitno, Galih Priyambada, Rudi Hartono (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study was to obtain valid test assessment and measurement instruments to identify the advantages and disadvantages of the dominant basic motion of children with mild impairment. This research includes types of research and development. This study took place in 6 months, this research through3 stages, namely (1) preliminary study stage, (2) drafting stage, (3) trial stage. The population in this study was SLB Tuna Grahita in Langkat Regency and Medan City. The results of the study obtained the standard of dominant basic motion assessment norms for children with mild categorytuna grahita . among them; Male locomotor movements (?39 = Good, 35-38 = Enough, ?34= Less), Women’s group (?37 = Good, 34-36 = Enough, ?33= Less). Motion Non Locomotor group of men (?34 = Good, 31-33 = Enough, ?30= Less), women’s group (?33 = Good, 30-32 = Enough, ?27= Less). Manipulative Motion of the male group (?50 = Good, 40-49 = Enough, ?39= Less), women’s group (?48 = Good, 39-47 = Enough, ?38= Less).